Importance of storage temperature control in refrigerated propane tanks - Sornoza Mera, José Antonio (2022)
The objective of this research article was to analyze the importance of controlling the storage temperature in refrigerated propane tanks, through a bibliographic review of updated documents and according to the subject under study. As a way to achieve the obtaining of knowledge, the qualitative paradigm was used as an interpretive approach as a documentary-bibliographical methodology. As a way to carry out this research, a search was carried out on digital platforms through key descriptors, related to renewable energy, sustainability, energy, rural sector. Inclusion criteria were used for the selection of the works, accessing a total of 05 investigations for the bibliometric analysis. It is concluded that there are some recommendations in the case of propane, specifically keep P210 away from heat, hot surfaces, sparks, open flames and any other source of ignition, in addition to not smoking. P377, if there is a burning gas leak: do not extinguish, unless the leak can be stopped without danger. The other type is the P381, for this it is suggested to eliminate all sources of ignition if it is safe to do so. Finally, in the case of P410+P403, protect from sunlight, store in a well-ventilated place.